PROSES PEMBENTUKAN BUDAYA TINGGALAN ARKEOLOGI DI KABUPATEN BADUNG - Putu Eka Juliawati (Balai Arkeologi Bali, 2015)
Archaeological remains in Bali commonly are still being used by society until now. Those remains experienced cultural processes before entering current systemic context. The aim of this research is to understand cultural formation process of archaeological remains, including its means and functions. The data were collected through observation, interview, and literature study. Analysis was done through classification of field data, and then presented in descriptive-qualitative method. Archaeological remains, which are discussed here, are personification statue, Ganesa statue, lingga, and stambha. Those artefacts have functions in social system of society, both in the past and present, although some of the artefacts had experienced disposal or abandonment process.Tinggalan arkeologi di Bali kebanyakan masih difungsikan sampai saat ini. Tinggalan tersebut mengalami proses budaya yang panjang hingga masuk ke dalam konteks sistem sekarang. Penelitian ini bertujuan untuk mengetahui proses pembentukan budaya tinggalan arkeologi tersebut, termasuk dinamika fungsi dan maknanya. Data dikumpulkan melalui observasi, wawancara, dan studi pustaka. Analisis dilakukan melalui pengklasifikasian data lapangan, kemudian disajikan secara deskriptif-kualitatif. Tinggalan arkeologi yang dibahas adalah arca perwujudan, Arca Ganesa, lingga, dan stambha. Benda tersebut berfungsi dalam sistem sosial masyarakat masa lalu dan masa kini, meskipun sebagian pernah mengalami proses buang atau ditinggalkan.